Revitalizing Islamic Law in the Era of Civilizational Crisis: The Role of Transformational Da'wah in Realizing Sharia Order in Indonesia - Widoyo, Agus Fatuh; Anang, Moh. Sitoh; Mastori, Mastori (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
The current global civilization, dominated by the secular-capitalist system, has given rise to multidimensional crises, such as moral decadence, socio-economic inequality, and spiritual alienation within society, a phenomenon also felt in Indonesia. In this context, the revitalization of Islamic law is an urgent need as a primary solution to the shortcomings of the secular-capitalist system, particularly in achieving justice, prosperity, and collective piety. This study aims to analyze how transformational da'wah tactics can be used as a means to establish Islamic law amidst the current of secular-capitalist domination. This study employs a qualitative research approach, utilizing a literature review methodology. Therefore, the works of key thinkers and literature on Islamic law, as well as critiques of capitalism, serve as primary sources. Meanwhile, secondary data includes articles, books, and supporting scientific articles. Data collection was conducted by searching relevant literature and documents. Data analysis was conducted both descriptively and analytically by examining key concepts in transformational da'wah and assessing their relevance to Indonesia's socio-political dynamics. This research finds that transformational da'wah, oriented toward ideological renewal and social practice, is crucial for grounding Islamic law amidst the identity and morality crisis of modern society. Transformation is not merely symbolic but also based on a shift in the mindset of the community regarding Islamic ideological awareness as an alternative to the dominance of secular capitalism, which is materialistic and individualistic. To achieve this, transformational da'wah offers three main strategies: developing critical awareness, strengthening the epistemological basis of Islam, and strengthening the da'wah community.